PERFORMANCE ANALYSIS OF SCHOOL BASED FINANCIAL MANAGEMENT IN SDIT IQRA'1 BENGKULU - Wagini, Abdul Rahim (Institut Agama Islam Bengkulu, 2016)
This study aims to determine the analysis of financial management performance in assessing the performance of School Based Management. The object of the research was conducted at SDIT IQRA'1 Kota Bengkulu. The importance of Financial Performance Management Analysis is done, so that the existing funds can be utilized optimally with more consider the calculation of incoming funds and funds issued. Data collection in this study using questionnaires and documentation. The data collected is processed by using descriptive qualitative analysis to know the performance of School Based Management in School Financial Management Performance Analysis. Based on the results of research decisions on the results of Respondents Respondents Teachers, staff, Structure, Employees, Committees in SDIT IQRA'1 and Foundation Al Fida Foundation to SDIT IQRA'1 of the four Indicators that become a benchmark for SDIT IQRA'1 city Bengkulu . To assess the Financial Management Performance Analysis of School Based Management with a score of Very Good criteria that is 4.55 indicates that the performance of management of School Based Management Finance is Very Good.Keywords: Management, Financial Management Planning, Budget Plan Process, and preparation of school budget plan.